Carrie Chapman Catt papers - Catt, Carrie Chapman, 1859-1947.
Correspondence, diaries, drafts of speeches and articles, subject files, biographical papers, newspaper clippings, printed material, and other papers relating primarily to Catt's efforts on behalf of the women's suffrage movement, feminism, and international peace. Also includes material on the Women's Centennial Congress of 1940 and the National Committee on the Cause and Cure of War. Diaries describe her travels to Africa, East Asia, Europe, and the Middle East.
Correspondents include Grace Abbott, Jane Addams, Viscountess Nancy Witcher Langhorne Astor, Newton Diehl Baker, Alice Stone Blackwell, Josephus Daniels, Charlotte Perkins Gilman, Ida Husted Harper, Mary Garrett Hay, Clara Hyde, Fiorello H. La Guardia, Julia Clifford Lathrop, Rosette Suzanne Manus, Katherine Dexter McCormick, Maud Wood Park, Mary Gray Peck, Helen Rogers Reid, Rose Schneiderman, Rosika Schwimmer, Edna Lamprey Stantial, Arthur Hays Sulzberger, William H. Taft, Joseph P. Tumulty, William Allen White, and Justina Leavitt Wilson.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Feminist, lecturer, and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Abbott, Grace, -- 1878-1939 -- Correspondence; Addams, Jane, -- 1860-1935 -- Correspondence; Astor, Nancy Witcher Langhorne Astor, -- Viscountess, -- 1879-1964 -- Correspondence; Baker, Newton Diehl, -- 1871-1937 -- Correspondence; Blackwell, Alice Stone, -- 1857-1950 -- Correspondence; Daniels, Josephus, -- 1862-1948 -- Correspondence; Gilman, Charlotte Perkins, -- 1860-1935 -- Correspondence; Harper, Ida Husted, -- 1851-1931. -- Correspondence; Hay, Mary Garrett, -- 1857-1928 -- Correspondence; Hyde, Clara -- Correspondence; La Guardia, Fiorello H. -- 1882-1947 -- Correspondence; Lathrop, Julia Clifford, -- 1858-1932 -- Correspondence; Manus, Rosette Suzanne, -- 1881-1942 -- Correspondence; McCormick, Katherine Dexter, -- 1876-1967 -- Correspondence; Park, Maud Wood, -- 1871-1955 -- Correspondence; Peck, Mary Gray, -- 1867?-1957 -- Correspondence; Reid, Helen Rogers, -- 1882-1970 -- Correspondence; Schneiderman, Rose, -- 1882-1972 -- Correspondence; Schwimmer, Rosika, -- 1877-1948 -- Correspondence; Stantial, Edna Lamprey -- Correspondence; Sulzberger, Arthur Hays, -- 1891-1968 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Tumulty, Joseph P. -- 1879-1954 -- Correspondence; White, William Allen, -- 1868-1944 -- Correspondence; Wilson, Justina Leavitt, -- -1955 -- Correspondence; National Committee on the Cause and Cure of War (U.S.); Feminism; Peace; Women -- Suffrage; Women's rights; Africa -- Description and travel; East Asia -- Description and travel; Europe -- Description and travel; Middle East -- Description and travel; Authors; Feminists; Lecturers